Tissue distribution of 35S-labelled perfluorobutanesulfonic acid in adult mice following dietary exposure for 1-5 days - Bogdanska, Jasna; Sundström, Maria; Bergström, Ulrika; Borg, Daniel; Abedi-Valugerdi, Manuchehr; Bergman, Åke; DePierre, Joseph; Nobel, Stefan (Elsevier, 2014)
Perfluorobutanesulfonyl fluoride (PBSF) has been introduced as a replacement for its eight-carbon homolog perfluorooctanesulfonyl fluoride (POSF) in the manufacturing of fluorochemicals. Fluorochemicals derived from PBSF may give rise to perfluorobutanesulfonic acid (PFBS) as a terminal degradation product. Although basic mammalian toxicokinetic data exist for PFBS, information on its tissue distribution has only been reported in one study focused on rat liver. Therefore, here we characterized the tissue distribution of PFBS in mice in the same manner as we earlier examined its eight-carbon homolog perfluorooctanesulfonate (PFOS) to allow direct comparisons. Following dietary exposure of adult male C57/BL6 mice for 1, 3 or 5d to 16 mg (35)S-PFBS kg(-1) d(-1), both scintillation counting and whole-body autoradiography (WBA) revealed the presence of PFBS in all of the 20 different tissues examined, demonstrating its ability to leave the bloodstream and enter tissues. After 5d of treatment the highest levels were detected in liver, gastrointestinal tract, blood, kidney, cartilage, whole bone, lungs and thyroid gland. WBA revealed relatively high levels of PFBS in male genital organs as well, with the exception of the testis. The tissue levels increased from 1 to 3 d of exposure but appeared thereafter to level-off in most cases. The estimated major body compartments were whole bone, liver, blood, skin and muscle. This exposure to PFBS resulted in 5-40-fold lower tissue levels than did similar exposure to PFOS, as well as in a different pattern of tissue distribution, including lower levels in liver and lungs relative to blood.